2016
DOI: 10.3171/2016.7.gks161549
|View full text |Cite
|
Sign up to set email alerts
|

Results of volume-staged fractionated Gamma Knife radiosurgery for large complex arteriovenous malformations: obliteration rates and clinical outcomes of an evolving treatment paradigm

Abstract: OBJECTIVEThere are few reported series regarding volume-staged Gamma Knife radiosurgery (GKRS) for the treatment of large, complex, cerebral arteriovenous malformations (AVMs). The object of this study was to report the results of using volume-staged Gamma Knife radiosurgery for patients affected by large and complex AVMs.METHODSData from 20 patients with large AVMs were prospectively included in the authors' AVM database between 2004 and 2012. A staging strategy was used when treating lesion volumes larger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…For relatively large AVMs >10 ml, two main treatment strategies have been suggested: One is a method in which the entire nidus is irradiated with a low dose, such as 14-16 Gy, and additional irradiation is considered after observing changes after several years (dose-staged radiosurgery: DS-SRS) [4]. Another method is VS-SRS, which divides a large nidus into several compartments and prescribes a reasonable dose to each compartment at intervals [2,3,[5][6][7][8][9]. Ilyas et al conducted a systematic review of VS-SRS and DS-SRS and reported that the average complete obliteration rate was 41.2% for VS-SRS and 32.3% for DS-SRS [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For relatively large AVMs >10 ml, two main treatment strategies have been suggested: One is a method in which the entire nidus is irradiated with a low dose, such as 14-16 Gy, and additional irradiation is considered after observing changes after several years (dose-staged radiosurgery: DS-SRS) [4]. Another method is VS-SRS, which divides a large nidus into several compartments and prescribes a reasonable dose to each compartment at intervals [2,3,[5][6][7][8][9]. Ilyas et al conducted a systematic review of VS-SRS and DS-SRS and reported that the average complete obliteration rate was 41.2% for VS-SRS and 32.3% for DS-SRS [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, for large AVMs, the prescribed dose should be decreased to reduce the risk of radiation damage, but it leads to a decrease in nidus obliteration rates. Therefore, it is very difficult to achieve complete obliteration of large AVMs in a single treatment, and methods using multiple irradiation have been reported previously [2][3][4][5][6][7][8][9]. 1 1…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of the ICON system, gamma knife radiosurgery has experienced its first trend toward frameless treatment strategies, as already embraced by Linac-based platforms [ 26 - 27 ]. As more patients receive treatment via this system, we are likely to see further reduction in the need for frame-based radiosurgery, especially in large lesions already treated with dose- or volume-fractionated SRS [ 28 - 29 ]. In our study, treatment remains a frame-based procedure, but the use of the 4D-CTA as part of the planning process in advance of frame placement demonstrates a significant reduction of “in frame” time.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma Knife radiosurgery (GKRS) is a safe and effective treatment modality for cerebral arteriovenous malformations (AVMs) that reduces the risk of bleeding, seizure, and some neurological deficits caused by stroke. [1][2][3][4][5][6][7][8][9][10] However, there is a risk of bleeding and radiation-induced perifocal edema and seizure before complete resolution of the nidus can be obtained with GKRS. 1,9,[11][12][13][14][15][16][17][18] Bleeding secondary to GKRS is usually caused by a residual AVM or recanalization of the organized intraluminal thrombus and hemodynamic changes (e.g., thrombosis or narrowing of the draining vein).…”
mentioning
confidence: 99%